Analisis Kompleksitas Dendam dalam Drama Hamlet Karya William Shakespeare: Indonesia - Lestari, Dewi Puspa; Sopandji, Nada Mutmainnah (STKIP PGRI Ponorogo Press, 2024)
In the play Hamlet by William Shakespeare, the motif of revenge becomes the central theme that determines the storyline. The purpose of this study is to determine the influencing factors, the role of doubt, and the impact on revenge in the play Hamlet. This study uses the textual analysis method to analyze the play Hamlet by William Shakespeare. The results show that Hamlet's doubt is the main factor that becomes an obstacle to revenge for his father's death. The role of Hamlet's doubt is based on internal and external obstacles as well as Hamlet's rational attitude towards mystical things that are not necessarily in accordance with the facts. Also the impact of revenge in William Shakespeare's Hamlet has significant implications for the end of the story with the killing of almost all the characters in it. The complexity of Hamlet's revenge shows that revenge can have various dimensions, both in terms of psychological, moral, and social.